Fiscal Year Ends and Nonlinear Incentive Contracts: The Effect on Business Seasonality - Oyer, P. (Quarterly Journal of Economics, 1998)
Salesperson and executive compensation contracts typically specify a nonlinear relationship between firm revenues and pay. These agents therefore have incentive to manipulate prices, influence the timing of customer purchases, and vary effort over their firms' fiscal years. This paper empirically establishes results consistent with agents' focusing on performance over the fiscal year. Most notably, in addition to varying with the calendar business cycle, manufacturing firms' sales are higher at the end of the fiscal year, and lower at the beginning, than they are in the middle. Further evidence is found in fiscal-year price movements and patterns in the industry variation of fiscal-year effects.